A turn‐off fluorescent substrate for horseradish peroxidase improves the sensitivity of ELISAs. Issue 2 (8th September 2014) - Acharya, Abhinav P.; Sen, Payel; Aran, Kiana; Gardner, Austin B.; Rafi, Mohammad; Dean, Deborah; Murthy, Niren
<x xml:space="preserve">Abstract</x> A new turn‐off fluorescent substrate for horseradish peroxidase is introduced, termed clics, which enhances the sensitivity of commercial enzyme‐linked immunosorbant assays (ELISA) by 32‐fold and detects chlamydial infections in patients. Clics are cost‐effective, stable, and can be easily incorporated in commercial ELISA kits, and therefore should have a great impact in the fields of medicine and biology. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>